Exercise reduces airway sodium ion reabsorption in cystic fibrosis but not in exercise asthma - Schmitt, Laurenz Christofer; Wiebel, Matthias; Frese, Falko; Dehnert, Christoph; Zugck, Christian; Bärtsch, Peter; Mairbäurl, Heimo (The European respiratory journal, 2011)
When ventilating large volumes of air during exercise, airway fluid secretion is essential for airway function. Since these are impaired in cystic fibrosis and exercise-induced asthma, it was the aim of this study to determine how exercise affects airway Na+ and Cl- transport and whether changes depend on exercise intensity. - Nasal potential was measured in Ringer’s solution, with amiloride to block Na+ transport, and in low chloride-containing isoproterenol to assess Cl- channels. Nasal potential was measured at rest and during submaximal and maximal bicycle ergometer exercise in individuals with cystic fibrosis, exercise-induced asthma and controls. - At rest, nasal potential was significantly higher in cystic fibroses than in the others. Maximal exercise decreased nasal potentials in cystic fibrosis and controls but not in exercise asthma. Submaximal exercise decreased nasal potentials only in cystic fibrosis. Cl- transport was not affected. - Our results indicate that nasal potentials and Na+ transport were decreased by maximal exercise in healthy and cystic fibrosis, whereas submaximal exercise decreased potentials in cystic fibrosis only. Exercise did not affect nasal potentials in asthmatics. Decreased reabsorption during exercise might favour airway fluid secretion during hyperpnoea. This protective effect appears blunted in patients with exercise-induced asthma.
Gesehen am 12.10.2022